2011
DOI: 10.1007/s00431-011-1651-y
|View full text |Cite
|
Sign up to set email alerts
|

Panton–Valentine leukocidin-associated Staphylococcus aureus necrotizing pneumonia in infants: a report of four cases and review of the literature

Abstract: Four children under 16 months of age presented within an 18-month period with severe, rapidly progressive Panton-Valentine leukocidin-associated ST93 Staphylococcus aureus necrotizing pneumonia. Two of the cases that required extracorporeal membranous oxygenation and proved fatal had poor prognostic features of leukopenia, rash and pulmonary haemorrhage. All four cases had recent contact with S. aureus infection in a family member. Reported cases of S. aureus necrotizing pneumonia in infants are reviewed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
(60 reference statements)
0
22
1
1
Order By: Relevance
“…1,2,7 Pulmonary manifestations of MRSA have been described previuosly 2,8 and usually include empyema or lung abscess, but more often multiple, thin-walled, air-filled, cystlike foci, often referred to as pneumatoceles, which are seen as sequelae from acute pneumonia due to MRSA. 1,2,4,6,9 Although the mean age of S. aureus pneumonia is typically approximately 9 months 1,2,8 (range, 3.5 mo to 4 y), this infection is increasingly being seen in younger age groups.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…1,2,7 Pulmonary manifestations of MRSA have been described previuosly 2,8 and usually include empyema or lung abscess, but more often multiple, thin-walled, air-filled, cystlike foci, often referred to as pneumatoceles, which are seen as sequelae from acute pneumonia due to MRSA. 1,2,4,6,9 Although the mean age of S. aureus pneumonia is typically approximately 9 months 1,2,8 (range, 3.5 mo to 4 y), this infection is increasingly being seen in younger age groups.…”
Section: Discussionmentioning
confidence: 98%
“…20 The role of intravenous immunoglobulin (IVIG) in the treatment of S. aureus pneumonia is still not established, 1,17 although in vitro studies have shown that immunoglobulins neutralize the effect of PVL on polymorphonuclear neutrophils. 21 Given this beneficial effect, current United Kingdom guidelines recommend the use of IVIG for severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…of cases)Pneumothorax (No. of cases)ARDSECMOHFOVProne positionSurgerySurvivalSurvival with ECMOPanchabhai, 2015 [18]1 adult110010Right lung up1 left pneumonectomy1/11/1Schwartz, 2012 [19]4 infants44342NRNR02/40/2Noah, 2010 [2]2 adults2 adolescents443441NR2 thoracotomy4/44/4Castaldo, 2007 [20]8 childrenNR7474NRNRNR4/81/4Stroud, 2007 [1]2 childrenNR21221NR02/22/2This case1 adult111111101/11/1Total20 patiens4 adults16 children/adolescents100%(10/10)95%(19/20)60%(12/20)90%(18/20)70%(14/20)37.5%(3/8)50%(1/2)25%(3/12)70%(14/20)64%(9/14) PVL Panton-Valentine leukocidin, MRSA methicillin resistant Staphylococcus aureus , ARDS acute respiratory distress syndrome, ECMO extracorporeal membrane oxygenation, HFOV high frequency oscillatory ventilation, NR not reported …”
Section: Review Of Cases From the Literaturementioning
confidence: 99%